Diabetes as a cardiovascular risk factor: An overview of global trends of macro and micro vascular complications. (29th August 2020) - Dal Canto, Elisa; Ceriello, Antonio; Rydén, Lars; Ferrini, Marc; Hansen, Tina B; Schnell, Oliver; Standl, Eberhard; Beulens, Joline WJ
Abstract: The global prevalence of diabetes is predicted to increase dramatically in the coming decades as the population grows and ages, in parallel with the rising burden of overweight and obesity, in both developed and developing countries. Cardiovascular disease represents the principal cause of death and morbidity among people with diabetes, especially in those with type 2 diabetes mellitus. Adults with diabetes have 2–4 times increased cardiovascular risk compared with adults without diabetes, and the risk rises with worsening glycaemic control. Diabetes has been associated with 75% increase in mortality rate in adults, and cardiovascular disease accounts for a large part of the excess mortality. Diabetes-related macrovascular and microvascular complications, including coronary heart disease, cerebrovascular disease, heart failure, peripheral vascular disease, chronic renal disease, diabetic retinopathy and cardiovascular autonomic neuropathy are responsible for the impaired quality of life, disability and premature death associated with diabetes. Given the substantial clinical impact of diabetes as a cardiovascular risk factor, there has been a growing focus on diabetes-related complications. While some population-based studies suggest that the epidemiology of such complications is changing and that rates of all-cause and cardiovascular mortality among individuals with diabetes are decreasing in high-income countries, the economic and social burden of diabetes is expected to rise due to changing demographics and lifestyle especially in middle- and low-income countries. In this review we outline data from population-based studies on recent and long-term trends in diabetes-related complications.